2008
DOI: 10.1097/wnr.0b013e3283112720
|View full text |Cite
|
Sign up to set email alerts
|

Greater regional cortical gray matter thickness in obsessive-compulsive disorder

Abstract: Earlier studies are inconsistent regarding the structural basis of obsessive-compulsive disorder (OCD), and few studies have investigated whether patients with OCD have cortical thickness abnormalities compared with healthy volunteers. Using magnetic resonance imaging we compared regional differences in cortical thickness among 21 patients with OCD and 21 demographically matched healthy volunteers. Our findings indicate that the right inferior frontal cortex and posterior middle temporal gyrus are thicker in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…It is compelling that although other SBA studies 21,23,25,26,30,31 found grey matter thickness to be affected in patients with OCD, our results did not show such alterations in this measure, but we did find partly similar alterations in other measures. However, when interpreting these divergent results one needs to be aware that previous studies presented rather heterogeneous results as well.…”
Section: Comparison With Surface-based Studiescontrasting
confidence: 52%
“…It is compelling that although other SBA studies 21,23,25,26,30,31 found grey matter thickness to be affected in patients with OCD, our results did not show such alterations in this measure, but we did find partly similar alterations in other measures. However, when interpreting these divergent results one needs to be aware that previous studies presented rather heterogeneous results as well.…”
Section: Comparison With Surface-based Studiescontrasting
confidence: 52%
“…For example, Shin et al (Shin et al, 2007), examining OCD patients with long term treatment, have reported significant cortical thickness deficits in left inferior frontal, left middle frontal, left precentral, left superior temporal, left parahippocampal, left orbitofrontal and left lingual cortices. On the contrary, Narayan et al (Narayan et al, 2008) have demonstrated significantly increased thickness in right inferior frontal and posterior middle temporal cortices. In pediatric patients with OCD, reduced cortical thickness in left supramarginal gyrus has been observed in comparison with healthy controls (Fallucca et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…49 Using fMRI, Remijnse and colleagues 6 reported reduced APFC activity in patients with OCD during affective switching. Using structural MRI, Narayan and colleagues 50 showed a thicker posterior temporal gyrus in patients with OCD. They argued that the structural abnormalities might underlie poor neuronal connectivity, which in turn could affect information integration and cognitive functions in patients with OCD.…”
Section: Abnormal Intrinsic Functional Connectivity In Ocdmentioning
confidence: 99%